Association between non-alcoholic fatty liver disease-associated hepatic fibrosis and bone mineral density in postmenopausal women with type 2 diabetes or impaired glucose regulation - Mingfeng Xia; Xiaoyang Sun; Hua Bian; Xiaopeng Zhu; Hongmei Yan; Xinxia Chang; Linshan Zhang; Liu Wang; Xinyu Yang (BMJ Open Diabetes Research & Care, 2020)
Introduction To evaluate the association of non-alcoholic fatty liver disease (NAFLD)-associated hepatic fibrosis with bone mineral density (BMD) in postmenopausal women with type 2 diabetes mellitus (T2DM) or impaired glucose regulation (IGR).Research design and methods Two cohorts including 46 subjects with biopsy-proven NAFLD and 445 subjects with proton magnetic resonance spectrum-proven NAFLD were enrolled in this study. All subjects were postmenopausal women with T2DM or IGR. BMD at the lumbar spine L1–L4 and hip was measured using dual-energy X-ray absorptiometry. NAFLD fibrosis stage and NAFLD fibrosis score were used to evaluate the severity of liver fibrosis.Results In subjects with liver biopsy-proven NAFLD, BMD (T-score, Z-score and BMD value) in the advanced fibrosis group were significantly lower than that in the non-advanced fibrosis group (p<0.05). Fibrosis stage was negatively associated with T-score, Z-score and BMD value after adjusting for age, body mass index (BMI) and fasting plasma glucose (FPG). Additionally, fibrosis stage was independently associated with T-score, Z-score and BMD value after adjusting for age, BMI and FPG. These results were validated in a large cohort of 445 subjects. Additionally, bone metabolism-associated factors, including calcium and phosphate, were associated with liver fibrosis, indicating that bone metabolism may play a critical role in the association between liver fibrosis and BMD. Mechanically, parathyroid hormone and biomarkers of bone formation (osteocalcin and procollagen type 1 N-terminal propeptide) and bone resorption (procollagen type I carboxy terminal peptide β special sequence) were increased in subjects with advanced liver fibrosis than in subjects without advanced liver fibrosis, indicating that liver fibrosis decreased BMD probably via increasing bone turnover.Conclusions NAFLD-associated hepatic fibrosis was negatively associated with decreased BMD in postmenopausal women with T2DM or IGR. Liver fibrosis decreased BMD probably via increasing bone turnover. Severe liver fibrosis may represent high risk for osteoporosis in postmenopausal women with T2DM or IGR.